Script programming and online portal development to broadcast the Climate Smart Agriculture (CSA) indicators from the Climate Smart Village Monitoring (pilot for Olopa, Guatemala) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
The script programing to calculate the standard CSA indicators was undertaken for a single CSV site as "proof of concept". As the rolling out for the CSV monitoring plan was completed (with small context specific adjustments needed) we will now expand to include the results from the other CSVs.